2011
DOI: 10.1002/jcb.23337
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bone mineral density and reduced bone quality in H+/K+ATPase beta‐subunit deficient mice

Abstract: Proton pump inhibitors (PPIs) are widely used against gastroesophageal reflux disease. Recent epidemiological studies suggest that PPI users have an increased risk of fractures, but a causal relationship has been questioned. We have therefore investigated the skeletal phenotype in H(+) /K(+) ATPase beta-subunit knockout (KO) female mice. Skeletal parameters were determined in 6- and 20-month-old KO mice and in wild-type controls (WT). Whole body bone mineral density (BMD) and bone mineral content (BMC) were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
4
19
0
Order By: Relevance
“…Gastric anacidity has been suggested to affect bone metabolism through malabsorption of calcium, giving rise to secondary hyperparathyroidism. This is in accordance with our previous study on H + /K + ATPase beta subunit KO mice, showing higher plasma PTH in KO mice at 6 months of age (Fossmark et al 2012). A study by Schinke and coworkers revealed that CCK2-deficient mice also had an osteoporotic phenotype (Schinke et al 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Gastric anacidity has been suggested to affect bone metabolism through malabsorption of calcium, giving rise to secondary hyperparathyroidism. This is in accordance with our previous study on H + /K + ATPase beta subunit KO mice, showing higher plasma PTH in KO mice at 6 months of age (Fossmark et al 2012). A study by Schinke and coworkers revealed that CCK2-deficient mice also had an osteoporotic phenotype (Schinke et al 2009).…”
Section: Discussionsupporting
confidence: 92%
“…A number of large studies have reported increased risk of fractures in long-term users of PPIs (Vestergaard et al 2006, Yang et al 2006, Targownik et al 2008 Corley et al 2010, Gray et al 2010, Khalili et al 2012 and patients with chronic atrophic gastritis (Goerss et al 1992, Merriman et al 2010). Histing and coworkers demonstrated delayed fracture healing in mice given the PPI pantoprazole (Histing et al 2012), and our group has previously found reduced BMC, BMD and mechanical bone strength in H + /K + ATPase beta subunit KO mice (Fossmark et al 2012). Gastric hypoacidity and secondary hypergastrinemia are common features of PPI users, patients with chronic atrophic gastritis and the H + /K + ATPase beta subunit KO mice.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It could be well established that absence of leptin signaling results in a high bone mass in spite of a hypogonadism situation, underscoring the critical function of this hormone. Leptin, a powerful inhibitor of bone formation in vivo, is expressed in bone cells and involved in regulation of osteoblast differentiation and mineralization and is assumed to act on the ATP exchange in those cells via the H + /K + ATPase …”
Section: Polyp: a (Potential) Metabolic Fuel For Bone Mineralizationmentioning
confidence: 99%
“…It consists of an a subunit that contains the catalytic site and a b subunit that is necessary for targeting of the enzyme to the apical membrane. H þ K þ -ATPase b-subunit knockout female mice have gastric hypoacidity along with lower bone mineral content, bone mineral density, and bone quality compared to wild-type mice [39]. The findings support the proposed causal relationship between the use of PPIs and increased fracture risk in patients but cannot differentiate between a direct effect of the PPI and an indirect effect mediated by hypoacidity.…”
Section: H R K R -Atpasementioning
confidence: 76%